2015
DOI: 10.1016/j.ceramint.2015.03.043
|View full text |Cite
|
Sign up to set email alerts
|

A-site strontium doping effects on structure, magnetic, and photovoltaic properties of (Bi1−Sr )FeO3− multiferroic ceramics

Abstract: Raman spectroscopy, X-ray diffraction (XRD), magnetization hysteresis loop, synchrotron X-ray absorption spectroscopy, and photovoltaic effects have been measured in (Bi 1 À x Sr x )FeO 3 À δ (BFO100xSr) ceramics for x ¼0.0, 0.05, 0.10, and 0.15. Raman spectra and XRD reveal a rhombohedral R3c structure in all compounds. A-site Sr 2 þ doping increases fluctuations in cation-site occupancy and causes broadening in Raman modes. BFO15Sr exhibits a strong ferromagnetic feature due to reduction of Fe-O-Fe bond angl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…A-site substitutions of rare-earth elements onto the BiFeO 3 perovskite cell have been employed to enhance ferromagnetic, ferroelectric, and photovoltaic responses [8][9][10][11]. A-site substitutions of alkaline earth metal elements in BiFeO 3 , i.e., (Bi 1-x A x ) FeO 3 (A = Ca, Sr, Ba), have also demonstrated an improvement of magnetic and ferroelectric properties [12][13][14][15][16][17][18][19][20][21][22][23]. It was proposed that magnetization can be enhanced as the doping ion radius increases due to suppression of the antiferromagnetic spiral spin configuration in BiFeO 3 [23].…”
Section: Introductionmentioning
confidence: 99%
“…A-site substitutions of rare-earth elements onto the BiFeO 3 perovskite cell have been employed to enhance ferromagnetic, ferroelectric, and photovoltaic responses [8][9][10][11]. A-site substitutions of alkaline earth metal elements in BiFeO 3 , i.e., (Bi 1-x A x ) FeO 3 (A = Ca, Sr, Ba), have also demonstrated an improvement of magnetic and ferroelectric properties [12][13][14][15][16][17][18][19][20][21][22][23]. It was proposed that magnetization can be enhanced as the doping ion radius increases due to suppression of the antiferromagnetic spiral spin configuration in BiFeO 3 [23].…”
Section: Introductionmentioning
confidence: 99%
“…The density-functional-theory (DFT) calculation and X-ray absorption spectroscopy revealed that the A-site rare-earth lanthanum (La) doping in BFO can reduce the leakage current18. It has been reported that doping can be one of the most effective methods used to improve ferroelectric and magnetic properties19202122, as the Bi-site substitution can effectively control the volatility of Bi atoms with reduction of oxygen vacancies23 and enhancement of photovoltaic effects242526. For photovoltaic applications, the BFO should be able to absorb as much light as possible to generate a photocurrent, which requires a lower band gap and large absorption coefficient27.…”
mentioning
confidence: 99%
“…A high‐resolution TEM (JEM‐2100 LaB 6 , JEOL Ltd., Tokyo, Japan) was used to study the symmetry groups and domain structures. Micro‐Raman spectra were measured using a Raman instrument (XperRam 200; Nanobase Inc., Seoul, Korea) equipped with a green laser of λ = 532 nm . To determine the oxidation states, the synchrotron X‐ray absorption near‐edge structure (XANES) and extended X‐ray absorption fine structure (EXAFS) spectra of Fe K ‐ edge were recorded in transmission mode at the 01C1 beam line of the National Synchrotron Radiation Research Center in Taiwan.…”
Section: Methodsmentioning
confidence: 99%
“…BFO films and crystals have shown interesting photovoltaic (PV) responses and photoconductivity . PV properties of the alkaline‐earth (Ca 2+ , Sr 2+ , Ba 2+ )‐doped BFO ceramics with ITO (top) and Au (bottom) electrodes have shown dependences on thickness, light wavelength, and intensity . The PV open‐circuit voltage and short‐circuit current have been described by a theoretical model, which is based on the photo‐excited carriers in the interface …”
Section: Introductionmentioning
confidence: 99%